Millimeter-wave noise characterization of PHEMT devices. - Béland, Paul. (University of Ottawa (Canada), 1997)
The theoretical background of thermal noise representation in two-port networks is presented. From this theory, the existing measurement techniques to characterize the noise of pseudomorphic high electron mobility transistors (PHEMTs) at millimeter-wave frequencies are described. The techniques are applied to the now popular on-wafer measurement. A novel on-wafer resistive noise source (ORNS) which provides noise measurement capability at all frequencies from a single calibrated frequency is presented. Demonstration of the noise source capability is made by comparing the measurement of receiver noise figure and two-port noise parameter extraction with those of a coaxial noise source. A custom design of an on-wafer probing station featuring an adapter to directly connect an automated mechanical tuner to the on-wafer probe, and featuring double input and output probes, is evaluated for measurement of noise parameters from 26 to 40 GHz. The results obtained with two 150 $\mu$m parallel finger PHEMTs are presented and compared with the general trend of noise models and measurement on an independent system at 26 GHz. Uncertainty analysis is performed for the measurements made at 30 GHz using a commercial microwave computer aided design (CAD) software.
Keywords: Engineering, Electronics and Electrical.